COST-EFFECTIVENESS DEXKETOPROFEN VS KETOROLAC IN CAESAREAN PATIENTS AT 'X' HOSPITAL, PANDEGLANG - Yusransyah, Yusransyah; Sofi Nurmay, Stiani; Farahdina, Chairani; Latifah Nur, Rizki; Baha, Udin (Pharmacoscript, 2025)
Post-cesarean section pain must be treated promptly and appropriately to prevent chronic conditions. Dexketoprofen and Ketorolac are non-narcotic analgesics commonly used to manage such pain. This study aimed to analyse the cost-effectiveness of dexketoprofen and ketorolac in patients undergoing cesarean sections at Mother and Child Hospital "X" in Pandeglang. The study used a cross-sectional design with cost-effectiveness analysis, specifically the Average Cost-Effectiveness Ratio (ACER). Pain intensity was measured one hour after surgery using the Faces Pain Rating Scale and Visual Analog Scale (VAS). Inclusion criteria were patients who underwent cesarean section and received non-narcotic analgesics. A total of 90 patients participated: 39 in the dexketoprofen group and 51 in the ketorolac group. Data were analyzed using ACER and the Mann-Whitney test. The ACER, based on the Faces Pain Rating Scale, showed a cost of IDR 1,142 for the dexketoprofen group and IDR 958.03 for the ketorolac group. Using the VAS, the cost was IDR 1,110 for dexketoprofen and IDR 657.45 for ketorolac. Statistical results showed a p-value < 0.05 for both pain measurement tools, indicating a significant difference in effectiveness between the two therapies. Based on both instruments, ketorolac was more cost-effective than dexketoprofen in managing post-cesarean section pain. This finding suggests that ketorolac may be a preferable option in clinical settings where cost and effectiveness are key considerations for post-operative analgesia in cesarean section patients.